The recognition of a period of studies abroad as a determinant for learning mobility of female students of pedagogy - Mateusz Marciniak (Lubelski Rocznik Pedagogiczny, 2021)
Introduction: The implementation of the Bologna Process has contributed to the rising level of recognition of qualifications and study periods in higher education. Consequently, the level of student mobility increased (e.g. Erasmus+). Current research shows, that the recognition of courses completed abroad is important, yet not crucial factor that impacts mobility.